Differential Effects of Exercise Programs on Neuregulin 4, Body Composition and Cardiometabolic Risk Factors in Men With Obesity - Saeidi, Ayoub; Shishvan, Sevda R.; Soltani, Mohammad; Tarazi, Fatemeh; Doyle-Baker, Patricia K.; Shahrbanian, Shahnaz; Mollabashi, Shirin S.; Khosravi, Nikoo; Laher, Ismail; Moriarty, Terence A.; Johnson, Kelly E.; VanDusseldorp, Trisha A.; et al. (Frontiers in Physiology, 2022)
Background Neuregulin 4 (Nrg4) is an adipokine that is sensitive to energy expenditure and with a potential role in metabolic homeostasis and obesity. This study examined the effects of 12 weeks of three different exercise training protocols on Nrg4 levels, cardiometabolic risk factors, and body composition parameters in men with obesity. Methods Sixty adult men with obesity (Mean ± SD; age: 27.60 ± 8.4 yrs.; height: 168.4 ± 2.6 cm; weight: 96.7 ± 7.2 kg) were randomly allocated into four equal (n = 15) groups: High- Intensity Interval Training (HIIT), Circuit Resistance Training (CRT), Moderate Intensity Continuous Training (MICT) or a control group. The HIIT protocol involved six bouts of 3-min high-intensity exercise (90% VO2peak) followed by 3-min low-intensity exercise (50% VO2peak). The CRT group performed three circuits of resistance training, where each circuit included 11 exercises at 20% of one-repetition maximum (1RM) and 70% of VO2peak, and with a work-to-rest ratio of 2:1 (40-s exercise and 20-s rest) and 60-s recovery between circuits. The MICT group performed 36 min of exercise at 70% of VO2peak. All measurements were taken 72 h before and after the first and last training sessions. Results There were significant differences between the groups in fat-free mass (FFM), (effect size (ES): 0.78), fat mass (ES: 0.86), VO2peak (ES: 0.59), high-density lipoprotein cholesterol (HDL-C) (ES: 0.83), low-density lipoprotein (LDL-C) (ES: 0.79), total cholesterol (TC) (ES: 0.90), triglyceride (TG) (ES: 0.52) glucose (ES: 0.39), insulin (ES: 0.61), HOM-IR (ES: 0.91) and Nrg4 (ES: 0.98) (p < 0.05). There were no significant changes in very-low-density lipoprotein cholesterol (VLDL-C) (ES: 0.13) levels, or body weights (ES: 0.51) (p > 0.05). Levels of Nrg4 were negatively correlated with LDL-C, TC, TG, VLDL-C, glucose, insulin, HOMA-IR (p < 0.05) and positively with HDL-C (p < 0.05). Conclusion Our results suggest that HIIT and CRT protocols have greater effects than MICT protocol on Nrg4 levels, metabolic and cardiovascular risk factors, and body composition variables in men with obesity.